The Multipath Influence in Real-Time Kinematic of GNSS Observations at Different Antenna Heights - Nour, Bakheet Agab; Ozdemir, Ahmet Turan; Garang, Peter; Ağırbaş, Oğuzhan (Politeknik Elektronika Negeri Surabaya (PENS), 2019)
Multipath is a dominant error source in Real-Time Kinematic (RTK) applications that reduces the position, time and velocity accuracy. Mitigation of such errors can be achieved by better signal processing and antenna design. This paper attempts to examine the different height of RTK system antenna with regards to the multipath error. The results obtained in this work show height significantly change of multipath in pseudo range (MP1) and multipath in the carrier phase (MP2). Different antenna height does not give the same multipath error result in the tests that we have conducted in this work. The optimal height of the antenna was achieved as two meters in order to obtain a minimum multipath error for MP1 and MP2. At the end of this work, we experimentally proved that there is an inverse relationship between the height of the antenna and multipath with RTK algorithm.